Evaluation of an Evidence-based and Community-responsive Fatherhood Training Program: Providers' Perspective - Renice Obure, MPH; Hamisu M. Salihu, MD, PhD; Anjali Aggarwal, MD; Acara E. Turner, BS; Estrellita "Lo" Berry, MA; Deborah A. Austin, PhD; Usman J. Wudil, MD, MPH; Muktar H. Aliyu, MD, DrPH; Ronee E. Wilson, PhD (Global Health and Education Projects, Inc., 2019)
Background And Objectives: Studies on male involvement and pregnancy outcomes have often not incorporated the providers' perspectives, which are potentially critical to understanding program context, evolution, perceived impact, and sustainability. We sought to evaluate the 24/7 Dad® program from the viewpoint of the program providers. Methods: We conducted purposive sampling of 24/7 Dad program facilitators and administrators who were involved in recruitment, training, and follow up of program participants within a federal Healthy Start program (REACHUP) in Tampa, Florida, USA. Using a snowballing approach, we recruited six key informants who had administered the program for at least four years. We elicited and evaluated factors impacting the performance of the father involvement program using content analysis. Results: Under program participation and perceived impact, most providers thought that the program had created a safe space previously unavailable for men in the community. The most useful recruitment strategy was building partnerships with other organizations. The key informants noted an important evolutionary trend in the father involvement program over time as well as the nature of linkages to partner organizations within the area. Threats to program sustainability included the continued reluctance and scepticism to invest funds to address male issues, sub-optimal retention of participants who were living transient lives as well as geographical/transportation barriers. Conclusion and Global Health Implications: The involvement of fathers during pregnancy has significant implications for healthy babies. Our study results provide a clarion call to augment capacity and infuse more resources to improve paternal involvement in order to attain the United Nations Sustainable Goal (2015-2030) of ensuring healthy lives and the promotion of well-being for all at all ages. Key words: • Fatherhood involvement • Fatherhood training • REACHUP • Childhood development • 24/7 Dad program   Copyright © 2020 Obure et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.